Massive biventricular rhabdomyoma in a neonate - Manish Pandey; Rimlee Dutta; Shyam S Kothari (Wolters Kluwer Medknow Publications, 2017)
Rhabdomyoma is a well characterised entity in a neonate. Herein, we report a massive biventricular rhabdomyoma in a neonate presenting with cyanosis and congestive heart failure which was confirmed on autopsy. The report is for documentation of an unusually large tumour.